Self-generated validity and other effects of measurement on belief, attitude, intention, and behavior. - Feldman, Jack M.; Lynch, John G. (Journal of Applied Psychology, 1988)
Drawing from recent developments in social cognition, cognitive psychology, and behavioral decision theory, we analyzed when and how the act of measuring beliefs, attitudes, intentions, and behaviors affects observed correlations among them. Belief, attitude, or intention can be created by measurement if the measured constructs do not already exist in long-term memory. The responses thus created can have directive effects on answers to other questions that follow in the survey. But even when counterparts to the beliefs, attitudes, and intentions measured already exist in memory, the structure of the survey researcher's questionnaire can affect observed correlations among them. The respondent may use retrieved answers to earlier survey questions as inputs to response generation to later questions. We present a simple theory predicting that an earlier response will be used as a basis for another, subsequent response if the former is accessible and if it is perceived to be more diagnostic than other accessible inputs. We outline the factors that determine both the perceived diagnosticity of a potential input, the likelihood that it will be retrieved, and the likelihood that some alternative (and potentially more diagnostic) inputs will be retrieved. This article examines the effects of measurement operations on revealed correlations among survey measures of belief, attitude, intention, and behavior. The potential reactivity of measurement has long been of concern in psychology. Methodologists (e.g., Campbell & Stanley, 1966; Cook & Campbell, 1979; Runkel & McGrath, 1972) warn of measurement-induced distortions relating to social desirability, evaluation apprehension, and sensitization to experimental treatments. Although it is true that the problem of reactivity of measurement affects work in both the social and physical sciences, in the physical sciences, measurement effects are expressed in terms of substantive theory. For instance, Heisenberg's uncertainty principle links basic